PENINGKATAN KAPASITAS DAN KUALITAS PRODUKSI AMPIANG DI DESA SINAR JAYA KABUPATEN BANGKA - yuliyanto yuliyanto; Somawardi Somawardi (Jurnal Pengabdian Masyarakat Polmanbabel, 2022)
Ampiang is an authentic Bangka Belitung food made from tapioca, fish, water, salt and flavorings. Then in a round and thin shape with a diameter of 70 mm. You can find Ampiang bus at a warung or supermarket in Bangka Belitung. The objective of the Community Partnership Program (PKM) for the ampiang-making community groups is to improve the quality and production capacity of ampiang for partners. A survey has been conducted on ampiang making partners in Sinar Baru Sungailiat Village under the name "Ampiang Ikan Ciu Yu Erin". The problem that occurs to these partners is that the production equipment for the ampiang oil dryer at the partner is still manual, namely coating old paper or newspapers in the hope of reducing oil. So that ampiang does not last long and quickly causes mold and unpleasant odors. The method used is to make an Ampiang dryer with a capacity of 15 kg/process, which has a portable form so that it is easy to move around and conducts brief training on how to use and maintain an oil dryer. It is portable so it is easy to move around. As a result, Partners can increase the production of ampiang and this machine is able to produce ampiang which is more durable, more than 5 months. Based on the test results with a capacity of 15 kg Ampiang, 1000 rpm rotation, processing time of 5 minutes produces an average of 14.45 kg of dry Ampiang and 0.52 oil that has been separated. This means that every 1 kg of ampiang produces 0.036 kg of oil. This oil is what makes ampiang not durable and causes an unpleasant odor. This is also evidenced by the evaluation of ampiang's resistance for 5 months that has not shown any fungus attached to the ampiang.